The Effectiveness of Polydioxanone (PDO) Thread-Embedding Acupuncture in Adult Patients with Obesity: Case reports - Irma Nareswari; Diana Marsha Fredy; Cindy Notonegoro; Fieka Meitaqwatiningarum (Indonesian Nutrition Association, 2023)
Background: Obesity is a chronic condition defined as excess body fat which is diagnosed based on body mass index, abdominal circumference, and is associated with an increased risk of various diseases. Conservative management is often hard to comply with, unsuccessfully, and expensive, while acupuncture with its variety of modalities can be an option. Case: A therapy with polydioxanone thread embedding on acupuncture points along with other acupuncture modalities were performed in three cases of obese patients according to their etiology and conditions. Results: Based on the three cases of obese patients with PDO thread embedding acupuncture alone or combined with cupping, plum blossom and moxibustion modalities are beneficial in decreasing abdominal circumference. The effect after 2 months follow up respectively using abdominal circumference measurement 5 cm above the umbilicus -2 cm ( from 110 to 99cm);- 3 cm (from 90 to 87 cm); -8 cm (from 88 to 80 cm), umbilicus to umbilicus -6 cm (from 107 to 101 cm); 10 cm (from 103 to 93 cm); 7 cm (from 93 to 86 cm), 5 cm below umbilicus -1 cm (from 106 to 105 cm); -5 cm (from 107.5 to 102.5 cm); -6 cm (from 104 to 98 cm). No serious side effects occurred in the three cases. Conclusion: PDO thread embedding can be beneficial in treating obese patients. However, these results require further research.